Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Let's address this question step by step.
### Part (a): Finding the Domain
1. Domain of \( f(x) \):
- \( f(x) = 4x - 1 \)
- This is a linear function, and linear functions are defined for all real numbers.
- Domain of \( f \): \((-\infty, \infty)\)
2. Domain of \( g(x) \):
- \( g(x) = -5x^2 \)
- This is a quadratic function, and quadratic functions are defined for all real numbers.
- Domain of \( g \): \((-\infty, \infty)\)
3. Domain of \( f+g \):
- \( f+g(x) = f(x) + g(x) = 4x - 1 - 5x^2 \)
- This is a polynomial, and polynomials are defined for all real numbers.
- Domain of \( f+g \): \((-\infty, \infty)\)
4. Domain of \( f-g \):
- \( f-g(x) = f(x) - g(x) = 4x - 1 + 5x^2 \)
- This is a polynomial, and polynomials are defined for all real numbers.
- Domain of \( f-g \): \((-\infty, \infty)\)
5. Domain of \( fg \):
- \( fg(x) = f(x) \cdot g(x) = (4x - 1)(-5x^2) = -20x^3 + 5x^2 \)
- This is a polynomial, and polynomials are defined for all real numbers.
- Domain of \( fg \): \((-\infty, \infty)\)
6. Domain of \( ff \):
- We interpret \( ff(x) \) as \( f(x) \cdot f(x) = (4x - 1)(4x - 1) = 16x^2 - 8x + 1 \)
- This is a polynomial, and polynomials are defined for all real numbers.
- Domain of \( ff \): \((-\infty, \infty)\)
7. Domain of \( \frac{f}{g} \):
- \( \left(\frac{f}{g}\right)(x) = \frac{4x - 1}{-5x^2} \)
- The denominator \(-5x^2\) must not equal zero.
- \( x \neq 0 \)
- Domain of \( \frac{f}{g} \): \((-\infty, 0) \cup (0, \infty)\)
8. Domain of \( \frac{g}{f} \):
- \( \left(\frac{g}{f}\right)(x) = \frac{-5x^2}{4x - 1} \)
- The denominator \( 4x - 1 \) must not equal zero.
- \( 4x - 1 \neq 0 \)
- \( x \neq \frac{1}{4} \)
- Domain of \( \frac{g}{f} \): \( (-\infty, \frac{1}{4}) \cup (\frac{1}{4}, \infty) \)
So, the detailed domains are:
- \( f \): \( (-\infty, \infty) \)
- \( g \): \( (-\infty, \infty) \)
- \( f+g \): \( (-\infty, \infty) \)
- \( f-g \): \( (-\infty, \infty) \)
- \( fg \): \( (-\infty, \infty) \)
- \( ff \): \( (-\infty, \infty) \)
- \( \frac{f}{g} \): \( (-\infty, \infty) \), excluding \( x = 0 \)
- \( \frac{g}{f} \): \( (-\infty, \infty) \), excluding \( x = \frac{1}{4} \)
### Part (b): Finding the Composed Functions
Given \( f(x) = 4x - 1 \) and \( g(x) = -5x^2 \):
1. \( (f+g)(x) \):
- \( (f+g)(x) = f(x) + g(x) = 4x - 1 - 5x^2 \)
- So, \((f+g)(x) = -5x^2 + 4x - 1\)
2. \( (f-g)(x) \):
- \( (f-g)(x) = f(x) - g(x) = 4x - 1 - (-5x^2) \)
- So, \((f-g)(x) = 5x^2 + 4x - 1\)
3. \( (fg)(x) \):
- \( (fg)(x) = f(x) \cdot g(x) = (4x - 1)(-5x^2) \)
- So, \( (fg)(x) = -20x^3 + 5x^2 \)
4. \( (ff)(x) \):
- \( (ff)(x) = f(x) \cdot f(x) = (4x - 1)^2 \)
- So, \( (ff)(x) = 16x^2 - 8x + 1\)
5. \( \left(\frac{f}{g}\right)(x) \):
- \( \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} = \frac{4x - 1}{-5x^2} \)
- This is valid for \( x \neq 0\)
6. \( \left(\frac{g}{f}\right)(x) \):
- \( \left(\frac{g}{f}\right)(x) = \frac{g(x)}{f(x)} = \frac{-5x^2}{4x - 1} \)
- This is valid for \( x \neq \frac{1}{4} \)
### Evaluation at \( x = 1 \)
Let's evaluate each function at \( x = 1 \):
- \( f(1) = 4 \cdot 1 - 1 = 3 \)
- \( g(1) = -5 \cdot 1^2 = -5 \)
- \( ff(1) = (4 \cdot 1 - 1)^2 = 3^2 = 9 \)
- \( (f+g)(1) = -5 \cdot 1^2 + 4 \cdot 1 - 1 = -5 + 4 - 1 = -2 \)
- \( (f-g)(1) = 5 \cdot 1^2 + 4 \cdot 1 - 1 = 5 + 4 - 1 = 8 \)
- \( (fg)(1) = (4 \cdot 1 - 1)(-5 \cdot 1^2) = 3 \cdot -5 = -15 \)
- \( \left(\frac{f}{g}\right)(1) = \frac{4 \cdot 1 - 1}{-5 \cdot 1^2} = \frac{3}{-5} = -0.6 \)
- \( \left(\frac{g}{f}\right)(1) = \frac{-5 \cdot 1^2}{4 \cdot 1 - 1} = \frac{-5}{3} \approx -1.66667 \)
### Summary
- The domains:
- \( f \): \( (-\infty, \infty) \)
- \( g \): \( (-\infty, \infty) \)
- \( f+g \): \( (-\infty, \infty) \)
- \( f-g \): \( (-\infty, \infty) \)
- \( fg \): \( (-\infty, \infty) \)
- \( ff \): \( (-\infty, \infty) \)
- \( \frac{f}{g} \): \( (-\infty, \infty) \), excluding \( x = 0 \)
- \( \frac{g}{f} \): \( (-\infty, \infty) \), excluding \( x = \frac{1}{4} \)
- The values at \( x = 1 \):
- \( f(1) = 3 \)
- \( g(1) = -5 \)
- \( ff(1) = 9 \)
- \( (f+g)(1) = -2 \)
- \( (f-g)(1) = 8 \)
- \( (fg)(1) = -15 \)
- \( \left(\frac{f}{g}\right)(1) = -0.6 \)
- [tex]\( \left(\frac{g}{f}\right)(1) \approx -1.66667 \)[/tex]
### Part (a): Finding the Domain
1. Domain of \( f(x) \):
- \( f(x) = 4x - 1 \)
- This is a linear function, and linear functions are defined for all real numbers.
- Domain of \( f \): \((-\infty, \infty)\)
2. Domain of \( g(x) \):
- \( g(x) = -5x^2 \)
- This is a quadratic function, and quadratic functions are defined for all real numbers.
- Domain of \( g \): \((-\infty, \infty)\)
3. Domain of \( f+g \):
- \( f+g(x) = f(x) + g(x) = 4x - 1 - 5x^2 \)
- This is a polynomial, and polynomials are defined for all real numbers.
- Domain of \( f+g \): \((-\infty, \infty)\)
4. Domain of \( f-g \):
- \( f-g(x) = f(x) - g(x) = 4x - 1 + 5x^2 \)
- This is a polynomial, and polynomials are defined for all real numbers.
- Domain of \( f-g \): \((-\infty, \infty)\)
5. Domain of \( fg \):
- \( fg(x) = f(x) \cdot g(x) = (4x - 1)(-5x^2) = -20x^3 + 5x^2 \)
- This is a polynomial, and polynomials are defined for all real numbers.
- Domain of \( fg \): \((-\infty, \infty)\)
6. Domain of \( ff \):
- We interpret \( ff(x) \) as \( f(x) \cdot f(x) = (4x - 1)(4x - 1) = 16x^2 - 8x + 1 \)
- This is a polynomial, and polynomials are defined for all real numbers.
- Domain of \( ff \): \((-\infty, \infty)\)
7. Domain of \( \frac{f}{g} \):
- \( \left(\frac{f}{g}\right)(x) = \frac{4x - 1}{-5x^2} \)
- The denominator \(-5x^2\) must not equal zero.
- \( x \neq 0 \)
- Domain of \( \frac{f}{g} \): \((-\infty, 0) \cup (0, \infty)\)
8. Domain of \( \frac{g}{f} \):
- \( \left(\frac{g}{f}\right)(x) = \frac{-5x^2}{4x - 1} \)
- The denominator \( 4x - 1 \) must not equal zero.
- \( 4x - 1 \neq 0 \)
- \( x \neq \frac{1}{4} \)
- Domain of \( \frac{g}{f} \): \( (-\infty, \frac{1}{4}) \cup (\frac{1}{4}, \infty) \)
So, the detailed domains are:
- \( f \): \( (-\infty, \infty) \)
- \( g \): \( (-\infty, \infty) \)
- \( f+g \): \( (-\infty, \infty) \)
- \( f-g \): \( (-\infty, \infty) \)
- \( fg \): \( (-\infty, \infty) \)
- \( ff \): \( (-\infty, \infty) \)
- \( \frac{f}{g} \): \( (-\infty, \infty) \), excluding \( x = 0 \)
- \( \frac{g}{f} \): \( (-\infty, \infty) \), excluding \( x = \frac{1}{4} \)
### Part (b): Finding the Composed Functions
Given \( f(x) = 4x - 1 \) and \( g(x) = -5x^2 \):
1. \( (f+g)(x) \):
- \( (f+g)(x) = f(x) + g(x) = 4x - 1 - 5x^2 \)
- So, \((f+g)(x) = -5x^2 + 4x - 1\)
2. \( (f-g)(x) \):
- \( (f-g)(x) = f(x) - g(x) = 4x - 1 - (-5x^2) \)
- So, \((f-g)(x) = 5x^2 + 4x - 1\)
3. \( (fg)(x) \):
- \( (fg)(x) = f(x) \cdot g(x) = (4x - 1)(-5x^2) \)
- So, \( (fg)(x) = -20x^3 + 5x^2 \)
4. \( (ff)(x) \):
- \( (ff)(x) = f(x) \cdot f(x) = (4x - 1)^2 \)
- So, \( (ff)(x) = 16x^2 - 8x + 1\)
5. \( \left(\frac{f}{g}\right)(x) \):
- \( \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} = \frac{4x - 1}{-5x^2} \)
- This is valid for \( x \neq 0\)
6. \( \left(\frac{g}{f}\right)(x) \):
- \( \left(\frac{g}{f}\right)(x) = \frac{g(x)}{f(x)} = \frac{-5x^2}{4x - 1} \)
- This is valid for \( x \neq \frac{1}{4} \)
### Evaluation at \( x = 1 \)
Let's evaluate each function at \( x = 1 \):
- \( f(1) = 4 \cdot 1 - 1 = 3 \)
- \( g(1) = -5 \cdot 1^2 = -5 \)
- \( ff(1) = (4 \cdot 1 - 1)^2 = 3^2 = 9 \)
- \( (f+g)(1) = -5 \cdot 1^2 + 4 \cdot 1 - 1 = -5 + 4 - 1 = -2 \)
- \( (f-g)(1) = 5 \cdot 1^2 + 4 \cdot 1 - 1 = 5 + 4 - 1 = 8 \)
- \( (fg)(1) = (4 \cdot 1 - 1)(-5 \cdot 1^2) = 3 \cdot -5 = -15 \)
- \( \left(\frac{f}{g}\right)(1) = \frac{4 \cdot 1 - 1}{-5 \cdot 1^2} = \frac{3}{-5} = -0.6 \)
- \( \left(\frac{g}{f}\right)(1) = \frac{-5 \cdot 1^2}{4 \cdot 1 - 1} = \frac{-5}{3} \approx -1.66667 \)
### Summary
- The domains:
- \( f \): \( (-\infty, \infty) \)
- \( g \): \( (-\infty, \infty) \)
- \( f+g \): \( (-\infty, \infty) \)
- \( f-g \): \( (-\infty, \infty) \)
- \( fg \): \( (-\infty, \infty) \)
- \( ff \): \( (-\infty, \infty) \)
- \( \frac{f}{g} \): \( (-\infty, \infty) \), excluding \( x = 0 \)
- \( \frac{g}{f} \): \( (-\infty, \infty) \), excluding \( x = \frac{1}{4} \)
- The values at \( x = 1 \):
- \( f(1) = 3 \)
- \( g(1) = -5 \)
- \( ff(1) = 9 \)
- \( (f+g)(1) = -2 \)
- \( (f-g)(1) = 8 \)
- \( (fg)(1) = -15 \)
- \( \left(\frac{f}{g}\right)(1) = -0.6 \)
- [tex]\( \left(\frac{g}{f}\right)(1) \approx -1.66667 \)[/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.